Propriedades e aplicações recentes das ciclodextrinas Properties and recent applications of cyclodextrins - Cristina de Garcia Venturini; Jaqueline Nicolini; Clodoaldo Machado; Vanderlei Gageiro Machado (Química Nova, 2008)
Cyclodextrins (CDs) are cyclic oligosaccharides comprised of six or more glucose units connected by alpha-1,4 bonds. They have hydrophobic cavities with a hydrophilic exterior, and are versatile receptors for a variety of substrates. This ability allows them to be applied in many fields, as distinct as supramolecular chemistry, nanotechnology, pharmaceuticals, green chemistry, agrochemicals, analytical chemistry, toiletries, foods, and cosmetics. This review summarizes several aspects related to the physico-chemical properties of CDs and discusses their potential applications illustrated by recent examples. The prospects for their use in several areas are also described.